BIOREMEDIATION OF HEAVY METALS CONTAMINATED SOIL FROM A STEEL ROLLING COMPANY IN IBADAN (2016)
The accumulation and persistence of Heavy Metals (HMs) in soil poses serious environmental challenges. These HMs may leach and impair surface and ground water quality as well as bioaccumulate in plants. The burden of HMs in the environment can be reduced by Organic Amendment (OA) stimulated bacterial remediation. However, there is dearth of information on the treatment of HMs contaminated soil with OA stimulated microorganisms. This study was designed to bioremediate HMs contaminated soil using cattle dung slurry stimulated bacterial inoculum. Heavy metal contaminated soil samples were purposively collected from the surrounding of a steel rolling mill in Alomaja, Oluyole Local Government Area, Ibadan, Nigeria. Cattle dung slurry used as OA was collected from a commercial animal pen in Bodija Market, Ibadan. Bacteria were isolated from the soil using pour plate agar technique and identified using biochemical and molecular techniques. The isolates were screened to select high HMs tolerant strains used in remediation following standard techniques. The soil and OA samples were analysed for HM and sterilised using appropriate techniques. The sterilised soil was mixed with OA in ratio 5:1 and remediated with selected bacterial strains and thereafter Corchorus olitorius was planted for eight weeks using potted experiment. The experimental set up was completely randomised design of 16 groups consisting of sterilised mixture with three isolates (A, B, and C) singly and in combinations while Sterilised Soil (SS) only and Unsterilised Soil (US) with OA served as controls and each had five replicates. Agronomic parameters (Plant Height (PH), Stem Diameter (SD) and Number of Leaves (NL)) were monitored weekly under screen house conditions for eight weeks. Plants and composite soil for each study group were analysed for HMs thereafter. Data were analysed using descriptive statistics and ANOVA at α0.05. The soil was heavily contaminated with heavy metals, especially lead and chromium with concentrations of 1505.1-2333.6 and 1526.0-1678.7 mg/kg, respectively. Thirty-six bacteria isolates were identified as Pseudomonas (19), Proteus (5), Alcaligenes (5), Enterobacter (3), Providencia (2) and Bacillus (2). Alcaligenes aquatilis (A), Pseudomonas mucidolens (B) and Bacillus cereus (C) had high tolerance for HM (400-450 µg/mL) and were used for remediation. The results obtained for the PH, SD and NL in un-amended soil revealed a significant difference between ABC that had 7.84±0.69 cm, 1.35±0.00 mm, 5.8±0.45 and SS that had 4.10±0.55 cm, 1.33±0.04, 5.0±0.0, respectively. While in OA treated soil, BC had 9.24±1.78 cm, 1.35±0.00 mm, 5.60±0.55 and US had 22.94±4.30 cm, 2.20±0.20 mm and 9.40±1.82 for PH, SD and NL, respectively. Post bioremediation analysis of the soil samples revealed a reduction in the concentration of lead from 2333.55 to 20.8 and 22.6 mg/kg in B and ABC while chromium reduced from 1678.7 to 1.8 mg/kg in B. Postharvest analysis of C. olitorius revealed that percentage crude fibre, dry weight (g), lead and chromium concentration (mg/kg) in ABC and SS were 21.72±0.99, 0.99±0.17; 20.61±0.78, 0.63±0.24; 10.90±0.85, 4.15±0.64 and 9.15±0.64, 4.00±0.14, respectively. Pseudomonas mucidolens effectively remediated heavy metals contaminated soil and can be employed in the treatment of such contaminated environment.